Influence of electrical parameters and optimization of EDM performance measures on Ti-6A1-4V using DOE/TAGUCHI method - Md Zain, Mohd Zahiruddin (2005)
Advanced materials such as Titanium Alloys exhibit very excellent technical properties, however have only achieved partial acceptance in industrial application due to difficulties in machining. Advanced machining process such as Electrical Discharge Machining (EDM) is a potential process to machine such materials. However, lack of infonnation regarding machining process of those materials using EDM is a major constraint. In this work Channilles Technology Robofonn 100 die-sinking EDM was utilized to perfonn the machining of Ti-6AI-4 V and copper was used as the tool electrode. The focus of this work is the optimization of the EDM process variables where electrical parameters namely; intensity (I), pulse duration (Ii), pulse-off time (to) and open circuit voltage (U) were set as design factors. The effect of these design factors on EDM perfonnance measures or responses such as Material Removal Rate (MRR), Volumetric Electrode Wear Rate (EW) and surface roughness average (Ra) were studied and the optimum conditions and values of those responses were estimated. Beside that, the overall evaluation criteria (OEC) which represents all three responses into single index were also proposed at the finishing stage. Finally confinnation tests were conducted to verify the estimated values and all the experimental results fall within 10% error. Taguchi approach Design of Experiment (DOErraguchi) was utilized from planning until analyzing the results and to assists this work, DOE software; Qualitek 4 was utilized.